If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -3) = x + -17 Reorder the terms: x(-3 + x) = x + -17 (-3 * x + x * x) = x + -17 (-3x + x2) = x + -17 Reorder the terms: -3x + x2 = -17 + x Solving -3x + x2 = -17 + x Solving for variable 'x'. Reorder the terms: 17 + -3x + -1x + x2 = -17 + x + 17 + -1x Combine like terms: -3x + -1x = -4x 17 + -4x + x2 = -17 + x + 17 + -1x Reorder the terms: 17 + -4x + x2 = -17 + 17 + x + -1x Combine like terms: -17 + 17 = 0 17 + -4x + x2 = 0 + x + -1x 17 + -4x + x2 = x + -1x Combine like terms: x + -1x = 0 17 + -4x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-17' to each side of the equation. 17 + -4x + -17 + x2 = 0 + -17 Reorder the terms: 17 + -17 + -4x + x2 = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -4x + x2 = 0 + -17 -4x + x2 = 0 + -17 Combine like terms: 0 + -17 = -17 -4x + x2 = -17 The x term is -4x. Take half its coefficient (-2). Square it (4) and add it to both sides. Add '4' to each side of the equation. -4x + 4 + x2 = -17 + 4 Reorder the terms: 4 + -4x + x2 = -17 + 4 Combine like terms: -17 + 4 = -13 4 + -4x + x2 = -13 Factor a perfect square on the left side: (x + -2)(x + -2) = -13 Can't calculate square root of the right side. The solution to this equation could not be determined.
| x2/3-8x1/3-9=0 | | 3x^2-2x+82=0 | | 3x+12=9y | | X-6=x | | -.15x^2+90x=0 | | 90L-.15L^2=0 | | x-4=8x+3 | | 4x+9y = 4y+17 | | 0=2x^2+2 | | 4a+11/3=16a | | -3x-1=5-2x | | (5n+2)(2n-3)= | | 16x^4+6x^2= | | (3x-4)(x-2x^2-6)= | | (3-2y)(8-y)= | | (y-9)(y+9)= | | (m+1)(m+1)= | | (a-5)(a+3)= | | 3r(r-5)-2r(3r-1)= | | -2a(3a^2-4a-1)= | | 5(2x-11)+17=52 | | 5x(4x-3)= | | 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 |